Histopathological Overview of Kidney and Liver Female White Rat Administered (Ananas comosus var. microstachys L.) Extract as Herbal Plant for Dysmenorrhea - Fitmawati, Fitmawati; Saputra, Agus; Teruna, Hilwan Yuda; Juliantari, Erwina (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2024)
Abstract Dysmenorrhea is an important clinical as well as social problem affecting more than 50% of menstruating women. Nanas bongsai (Ananas comosus var. microstachys L.) is commonly used as a medical plant, which local people believe of Riau Province Indonesia, as medicine to reduce pain while the menstruation period (dysmenorrhea). This study was aim to find histopathologic changes in the kidney and liver after being treated with nanas bongsai extract in the female white rat. Design experimental of this research is complete randomized design with 5 treatments. Each treatment was composed of two control (zero control given with water, positive control given with mefenamic acid) and nanas bongsai extract with 3 different dosage serials. Histology preparations were made by paraffin method and Hematoxylin-Eosin staining. The results showed that given nanas bongsai extract with three serial dosages towards the kidney show a picnosis in the nucleus. However, this damage did not affect the glomerulus structure. While observation towards the liver shows some injury, namely hydropic degeneration, lipid degeneration, and necrosis. Both of these damaged less than 25%. As a result, this percentage did not affect the structure of the kidney and liver. The results of this study indicate that there is no damage to the kidneys and liver due to the use of nanas bongsai so it is safe to use in herbal medicine and can be developed as a dysmenorrhea drug.AbstrakDismenore merupakan masalah klinis dan sosial yang penting yang memengaruhi lebih dari 50% wanita menstruasi. Nanas bongsai (Ananas comosus var. microstachys L.) dipercayai oleh masyarakat Desa Muara lembu, Kabupaten Kuantan Singingi, Provinsi Riau sebagai obat untuk mengurangi nyeri saat haid (dismenore). Penelitian ini bertujuan untuk mengetahui perubahan histopatologi pada ginjal dan hati setelah diberi perlakuan ekstrak nanas bongsai pada tikus putih betina. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan 5 perlakuan. Masing-masing perlakuan terdiri dari dua kontrol dan ekstrak nanas bongsai dengan 3 seri dosis yang berbeda. Preparat histologi dibuat dengan metode parafin dan pewarnaan Hematoxylin-Eosin. Hasil penelitian menunjukkan bahwa pemberian ekstrak nanas bongsai dengan dosis tiga seri terhadap ginjal menunjukkan picnosis pada nukleus. Namun, kerusakan ini tidak memengaruhi struktur glomerulus. Sedangkan pengamatan terhadap hati menunjukkan beberapa cedera, yaitu degenerasi hidropik, degenerasi lipid, dan nekrosis. Keduanya rusak kurang dari 25%. Akibatnya, persentase ini tidak memengaruhi struktur ginjal dan hati. Hasil penelitian ini menunjukkan bahwa tidak ada kerusakan pada ginjal dan hati akibat penggunaan Nanas bongsai sehingga aman digunakan dalam pengobatan herbal dan dapat dikembangkan sebagai obat dismenore.